Long non-coding RNA SNHG22 regulated by SP1 is a potential biomarker for epithelial ovarian cancer diagnosis and regulates cell glycolysis - Xiao-Yan Liu; Li Deng; Xiao-Ling Wu; Xiao-Jing Tong (Clinical and Experimental Obstetrics & Gynecology)
Object: Long non-coding RNAs (lncRNAs) exert critical roles in cancer progression. However, the function of SNHG22 in epithelial ovarian carcinoma (EOC) still needs to be clarified. Methods: qRT-PCR was carried out to explore SNHG22 expression. Receiver operating characteristic (ROC) curve was used to evaluate the predictive ability. Glucose uptake and lactate secretion were used to monitor cancer cell glycolysis. Luciferase reporter and ChIP assays were conducted to investigate the molecular mechanism of SNHG22. Results: SNHG22 was found notably overexpressed in tumor tissues, cells and serum samples, which was regulated by SP1 with the stimulation of SNHG22 promoter activity. And SNHG22 expression in serum was an effective biomarker by ROC analysis. Moreover, SNHG22 facilitated glycolysis in EOC cells. Conclusions: Aberrant SNHG22 expression in serum could be used as a promising biomarker for EOC and SNHG22 promotes in glycolysis.